2017
DOI: 10.9758/cpn.2017.15.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Five Month-Persistent Extrapyramidal Symptoms following a Single Injection of Paliperidone Palmitate: A Case Report

Abstract: Long-acting injectable (LAI) antipsychotics are useful in the treatments for schizophrenic patients with poor adherence due to their maintaining feature of therapeutic plasma level without daily administrations. However, their long-lasting property can cause complicated problems such as a long-lasting side effect. We report a patient who experienced LAI-induced extrapyramidal symptoms (EPSs) for 5 months after a single injection. During that period, every trial to ameliorate this condition turned out to be a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Paliperidone is not metabolized by CYP 2D6 cytochrome system [3]. The nanocrystal molecules which make up the Paliperidone Palmitate suspension also allow it to undergo slow dissolution, yielding a half-life of 25–49 days [1, 4]. Treatment-emergent adverse effects (TEAEs) occurring more frequently in the Paliperidone Palmitate group than in the placebo group included insomnia, headache, dizziness, sedation, vomiting, injection site pain, extremity pain, myalgia, and extrapyramidal symptoms [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paliperidone is not metabolized by CYP 2D6 cytochrome system [3]. The nanocrystal molecules which make up the Paliperidone Palmitate suspension also allow it to undergo slow dissolution, yielding a half-life of 25–49 days [1, 4]. Treatment-emergent adverse effects (TEAEs) occurring more frequently in the Paliperidone Palmitate group than in the placebo group included insomnia, headache, dizziness, sedation, vomiting, injection site pain, extremity pain, myalgia, and extrapyramidal symptoms [4].…”
Section: Discussionmentioning
confidence: 99%
“…Long-acting injectable (LAI) antipsychotics are useful in the treatment of schizophrenic patients with poor medication adherence due to their maintaining feature of therapeutic plasma level without daily administration. However, their long-lasting property can cause complicated long-lasting side effects [1]. Paliperidone Palmitate is one of the long-acting injectable (LAI) antipsychotic drugs used for schizophrenic patients with poor medication adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only a single case study has reported that PP induced 5-month persistent EPSs after a single injection. 10 Oral paliperidone extended-release is generally an effective and well-tolerated therapy 13 and one of the first-line drugs to treat patients with schizophrenia. The incidence rates of EPSs, except for hyperkinesia, were found to be lower with PP than with oral paliperidone.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one previous case study reported that PP induced EPSs for 5 months after a single injection. 10 No studies to date, however, have reported the background of patients with schizophrenia in the case of PP-induced EPSs after 6 months. Consequently, this report also addresses the causes of EPSs by using several imaging techniques, namely magnetic resonance imaging (MRI) and dopamine transporter (DaT) scans, in the case of PP-induced EPSs in a patient with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%